2021
DOI: 10.1111/ppa.13369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the susceptibility of modern, wild, ancestral, and mutational wheat lines to Septoria tritici blotch disease

Abstract: Globally, bread wheat production is threatened by fungal diseases, including the devastating disease Septoria tritici blotch (STB). Given the global importance of STB, and the difficulty in identifying novel sources of resistance to this disease, we screened a variety of wheat genotypes, including wild, ancestral, and mutagenized lines, for their STB response. This delineated a panel of wild wheat relatives and Watkins collection lines with exceptional resistance to a range of Zymoseptoria tritici isolates, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…In different previous studies, the sources of Stb resistance genes were identified in wheat breeding material [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. As a consequence of molecular genetic tagging of resistance genes in 36 varieties of wheat, it was determined that the majority of the analyzed samples carried resistance genes ineffective against Z. tritici in their genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In different previous studies, the sources of Stb resistance genes were identified in wheat breeding material [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. As a consequence of molecular genetic tagging of resistance genes in 36 varieties of wheat, it was determined that the majority of the analyzed samples carried resistance genes ineffective against Z. tritici in their genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Additional techniques like genome editing ( Zhang et al., 2017 ) and Eco-Tilling ( Ajaz et al., 2021 ) have been increasingly utilized in wheat, having great potential to contribute to SB resistance breeding in near future.…”
Section: Biotechnological Approachesmentioning
confidence: 99%
“…The necrosis and the pycnidia that appear on the lesions can have diverse shapes, sizes, and colors. To exacerbate the complexity, these symptoms are highly dependent on Z. tritici isolates, wheat genotypes, and environmental conditions [ 9 ]. The latency period is another factor that makes STB symptoms difficult to detect.…”
Section: Introductionmentioning
confidence: 99%